Factors Influencing Tax Declaration Decisions on Social Networks of Online Retailers in Vietnam - Nguyen, Tran Hung; Xuan, Cu Le; Thi, Thuy Hang Vu (International Journal of Membrane Science and Technology, 2024)
The growth of e-commerce and online retail in Vietnam, particularly on social networks, has presented challenges for the government’s tax authorities. Preventing tax loss through inspections can be difficult due to missing or incomplete taxpayer data from transaction processing servers. Explaining undeclared or incompletely declared revenue in online trading transactions on the server or the Internet can be challenging, especially for retail activities and service provision for businesses and individuals selling on social networking. In Vietnam, the Tax Management Law 2019 established the tax rates online retailers must pay. However, tax collection for social network retailers still depends on tax authorities encouraging them to self-declare their revenue. Current research and practice show that very few sellers on social networks participate in the self-declaration of revenue to pay taxes. Moreover, few studies focus on factors affecting the participation of online retailers in Vietnam in tax declaration and payment, especially those selling on social networks, and most lack a solid theoretical foundation. Through a review of related studies, this research has identified several factors that affect tax payment decisions for retailers on social networks in Vietnam. The study also provides several recommendations to promote and enhance retailers’ tax declaration and payment decisions on social networks in Vietnam.